2016
DOI: 10.1161/circulationaha.115.016133
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Metabolite 16α-Hydroxyestrone Exacerbates Bone Morphogenetic Protein Receptor Type II–Associated Pulmonary Arterial Hypertension Through MicroRNA-29–Mediated Modulation of Cellular Metabolism

Abstract: Background Pulmonary arterial hypertension (PAH) is a proliferative disease of the pulmonary vasculature which preferentially affects females. Estrogens, such as the metabolite 16α-hydroxyestrone (16αOHE), may contribute to PAH pathogenesis; and, alterations in cellular energy metabolism associate with PAH. We hypothesized that 16αOHE promotes heritable PAH (HPAH) via miR-29 family upregulation, and that antagonism of miR-29 would attenuate pulmonary hypertension in transgenic mouse models of Bmpr2 mutation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 89 publications
4
78
0
Order By: Relevance
“…The data presented are important in their support of the relevance of current and future clinical trials targeting interventions on oestrogen signalling pathways. In addition, the study further solidifies the potential link between oestrogens and metabolic alterations in PAH [13].…”
supporting
confidence: 57%
“…The data presented are important in their support of the relevance of current and future clinical trials targeting interventions on oestrogen signalling pathways. In addition, the study further solidifies the potential link between oestrogens and metabolic alterations in PAH [13].…”
supporting
confidence: 57%
“…However, a recent study by CHEN et al [72] has indicated a possible role for the miR-29 family. In this study, exposure to 16αOHE led to increased expression of miR-29 in BMPR2 mutant mice.…”
Section: Oestrogen Signallingmentioning
confidence: 99%
“…Instead, targeting the pathways downstream of E2, e.g. the miR-29 family, may provide a means of treating PAH without the need to modulate sex hormones directly [72].…”
Section: Oestrogen Signallingmentioning
confidence: 99%
“…A sex-specific decrease in miR-96 was found to increase expression of the 5-hydroxytryptamine 1B receptor (42), thus predisposing to alteration of serotonin signaling and proliferative signals in the diseased pulmonary vasculature. Separately, a sex-specific interaction of miR-29 was described with estrogen metabolism (43), suggesting a molecular mechanism correlating female hormone signaling with the predisposition of PAH in women in the general population.…”
Section: Vasoconstrictionmentioning
confidence: 99%